Europe invades the hinterland: the impact of the arrival of Italian immigrants in the city of Jau (1853-1914) - Arlanch Martins De Oliveira, Flavia (Presses Univ Mirail, 2012)
We try to show what were the life conditions in the town of Jail's initial settlement, in the interior of Sao Paulo's state. Afterwards, we deal with the elements which brought about developement in this region : the coffee expansion, the coming of railways and the installation of italian immigrates in the city. We put the accent on the part this immigrates played in Jim's modernisation and on the integration process between this newcomers and the caipira's society which welcomed them.
Keywords: Jau; Caipira Society; Italian immigration; Coffee expansion; Cultural circularity